Dynamical transition in a large globular protein: Macroscopic properties and glass transition - Kealley, Cat; Sokolova, A.; Kearley, G.; Kermner, E.; Russina, M.; Faraone, A. (Elsevier, 2010)
Hydrated soy-proteins display different macroscopic properties below and above approximately 25%moisture. This is relevant to the food industry in terms of processing and handling. Quasi-elastic neutronspectroscopy of a large globular soy-protein, glycinin, reveals that a similar moisture-content dependence exists for the microscopic dynamics as well. We find evidence of a transition analogous to those found in smaller proteins, when investigated as a function of temperature, at the so-called dynamical transition. In contrast, the glass transition seems to be unrelated. Small proteins are good model systems for the much larger proteins because the relaxation characteristics are rather similar despite the change in scale. For dry samples, which do not show the dynamical transition, the dynamics of the methyl group is probably the most important contribution to the QENS spectra, however a simple rotational model is not able to explain the data. Our results indicate that the dynamics that occurs above the transition temperature is unrelated to that at lower temperatures and that the transition is not simply related to the relaxation rate falling within the spectral window of the spectrometer.